Macrophages Respond Rapidly to Ototoxic Injury of Lateral Line Hair Cells but Are Not Required for Hair Cell Regeneration - Warchol, Mark E.; Schrader, Angela; Sheets, Lavinia (Frontiers in Cellular Neuroscience, 2021)
The sensory organs of the inner ear contain resident populations of macrophages, which are recruited to sites of cellular injury. Such macrophages are known to phagocytose the debris of dying cells but the full role of macrophages in otic pathology is not understood. Lateral line neuromasts of zebrafish contain hair cells similar to those in the inner ear, and the optical clarity of larval zebrafish permits direct imaging of cellular interactions. In this study, we used larval zebrafish to characterize the response of macrophages to ototoxic injury of lateral line hair cells. Macrophages migrated into neuromasts within 20 min of exposure to the ototoxic antibiotic neomycin. The number of macrophages in close proximity of injured neuromasts was similar to that observed near uninjured neuromasts, suggesting that this early inflammatory response was mediated by ‘local’ macrophages. Upon entering injured neuromasts, macrophages actively phagocytosed hair cell debris. Such phagocytosis was significantly reduced by inhibiting Src-family kinases. Using chemical-genetic ablation of macrophages prior to ototoxic injury, we also examined whether macrophages were essential for the initiation of hair cell regeneration after neomycin exposure. Results revealed only minor differences in hair cell recovery in macrophage-depleted vs. control fish, suggesting that macrophages are not essential for the regeneration of lateral line hair cells.